The opportunities and challenges for nutritional intervention in childhood cancers - Wang, Kaiyue; Yang, Tianyou; Zhang, Yubin; Gao, Xiang; Tao, Ling (Frontiers in Nutrition, 2023)
Diet dictates nutrient availability in the tumor microenvironment, thus affecting tumor metabolic activity and growth. Intrinsically, tumors develop unique metabolic features and are sensitive to environmental nutrient concentrations. Tumor-driven nutrient dependencies provide opportunities to control tumor growth by nutritional restriction or supplementation. This review summarized the existing data on nutrition and pediatric cancers after systematically searching articles up to 2023 from four databases (PubMed, Web of Science, Scopus, and Ovid MEDLINE). Epidemiological studies linked malnutrition with advanced disease stages and poor clinical outcomes in pediatric cancer patients. Experimental studies identified several nutrient dependencies (i.e., amino acids, lipids, vitamins, etc.) in major pediatric cancer types. Dietary modifications such as calorie restriction, ketogenic diet, and nutrient restriction/supplementation supported pediatric cancer treatment, but studies remain limited. Future research should expand epidemiological studies through data sharing and multi-institutional collaborations and continue to discover critical and novel nutrient dependencies to find optimal nutritional approaches for pediatric cancer patients.